Insecticidal effects of the Olea europaea subsp. laperrinei extracts on the flour Pyralid Ephestia kuehniella - Lahcene, Souad; Taibi, Faiza; Mestar, Nadjet; Ali Ahmed, Samira; Boumendjel, Mahieddine; Ouafi, Saida; Houali, Karim (Cellular and Molecular Biology, 2018)
In the present study, the aerial parts of the Laperrine olive (Olea europaea subsp. Laperrinei) are subjected to acid extraction and the chemical composition of the extracts is determined by HPLC-DAD. The main compounds found in all of extracts are: hydroxytyrosol (30.45%), tyrosol (0.69%), oleuropein (32.76%), ferrulic acid (17.77%), quercetin (31.57%) and hesperetin (6.90%).The extracts obtained from the leafy stems of Laperrine olive tree are tested on the moth Ephestia kuehniella flour. Their administration by inhalation of newly exuviated chrysalises extends the duration of nymphalid development and disturbs the exuviated adults reproduction, by reducing the period in which the eggs are being laid. Thus, compared to the control insects, the number of eggs laid by treated females is significantly reduced after the treatment by extracts. Besides, the administration of different extracts of adult butterflies has a premature mortality effect.